ICP-PR Bee Brood Working Group – Variability of brood termination rates in reference to validity criteria and limited effectiveness of method improvement in honeybee semi-field studies (OECD GD 75) - Szczesniak, Bronislawa; Pilling, Ed; Bocksch, Sigrun; Becker, Roland; Lückmann, Johannes (Julius-Kühn-Archiv, 2018)
OECD Guidance Document 75 (2007) outlines a test method to assess effects of plant protection products (PPPs) on honeybee brood under semi-field conditions. The assessment of bee brood development is conducted by mapping cells containing eggs and following their development until emergence. Evaluated parameters are: brood termination rate (BTR), brood compensation index (CI) and brood index (BI). Due to high variability of BTRs within treatments and high control mortality in a number of studies no definite conclusions regarding effects on brood were possible in the past and studies needed to be repeated (Pistorius et al. 2012). To address this variance, effort was taken by ICP-PR and AG Bienenschutz to improve the method by further analyzing current and historical data considering possible influencing factors (Pistorius et al. 2012, Becker et al. 2015) to give recommendations for future testing. The main findings were that reliability of the test method was questionable and that further method improvement and data evaluation was required. Therefore in this paper data evaluation of studies conducted between 2014 and 2017 is carried out and potential key parameters influencing outcome of studies are given. To evaluate the improvement of the OECD 75 test method following the recommendations from 2015, a data analysis of 86 studies conducted in Germany, France, Spain and US was performed. The mean BTR value in the control group was 30.2% for studies conducted in Germany (mean of 61 studies), 19.4% in France (mean of 3 studies), 41.8% in Spain (mean of 5 studies) and 50.6% in US (mean of 17 studies). Results from Spain and US displayed higher BTRs in control compared to data from Germany. Evaluation of BTRs for Germany displayed only a slight improvement (historical value of 32.9%). Analysis of data shows a limitation of options to improve the method as no main driver for high variability of BTRs in the control group was found. The cause for low precision may be multifactorial and driven by “caging effect”. There are alternative test methods available to observe bee brood development, without confinement in the tunnels, under field conditions (Oomen et al. (1992), OECD GD 75 field test design). Therefore it is necessary to investigate differences between these open field methods and semi-field testing with regard to routes of exposure, residues in brood and brood mortality, to choose the most reliable and adequate testing method assessing potential effects of PPP on honeybee brood development.